The Golem, the Djinni, and ChatGPT: Artificial Intelligence and the Islamicate Occult Sciences - Inloes, Amina (Theology and science, 2025)
What do golems, talismans, and Artificial Intelligence (AI) share? How would Ibn Sīnā have classified ChatGPT? Must AI be de-mythologized, or can mythos help us navigate a strange new world? Why does AI seem occult, and is ChatGPT a pricey talisman? These questions offer insight into theological concerns about AI, including (1) human exceptionalism, (2) creating new beings, (3) objects knowing, and (4) metaphors other than a demon or demigod. This article examines AI through a classical Islamicate occult paradigm to better grasp what it is, metaphysically speaking, and how developments in AI might outmode some post-Enlightenment worldviews.